2015
DOI: 10.1007/s10815-015-0490-6
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to radiation therapy is associated with female reproductive health among childhood cancer survivors: a meta-analysis study

Abstract: Background and aims Many epidemiological studies have revealed a positive correlation between medical radiation exposure and the reproductive health in female childhood cancer survivors. However, because of variations in the samples size, such studies showed partly inconsistent conclusions. The aim of this meta-analysis was to clarify the association between radiotherapy and the risk of reproductive health impairment for female who survived from childhood cancer. Methods Fourteen cohort studies involving child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
(62 reference statements)
0
19
0
1
Order By: Relevance
“…The FCR contains complete information on chemotherapy and radiotherapy given within 4 months of diagnosis. Previous studies, however, have not detected a significant dose‐response association between radiotherapy or alkylating agents and congenital anomalies . Studies have demonstrated neither genomic instability nor germline minisatellite mutation associated with radiotherapy .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The FCR contains complete information on chemotherapy and radiotherapy given within 4 months of diagnosis. Previous studies, however, have not detected a significant dose‐response association between radiotherapy or alkylating agents and congenital anomalies . Studies have demonstrated neither genomic instability nor germline minisatellite mutation associated with radiotherapy .…”
Section: Discussionmentioning
confidence: 93%
“…However, this is a diagnostic group with a large variety of congenital anomalies and we had limited numbers of these Table 5. Prevalence ratios (PR) with 95% confidence intervals (CI) for association between the risk for any congenital anomaly and cancer of parent in young adulthood (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) 1 Observed number of offspring with any congenital anomaly. Only congenital anomalies in offspring recorded in the first 2 years of life were taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated, the dose needed to destroy a half of the primordial follicles (LD 50 ) is estimated at below 2 Gy [48] 55-3.17), which evidences that radiotherapy during childhood exerts a negative effect on reproductive health in adulthood. The importance of the time elapsed, as well as individual differences for the effects of radiation observed, requires further studies [100].…”
Section: Transgenerational Transmission Of Genomic Instabilitymentioning
confidence: 99%
“…Pelvic irradiation in childhood negatively affect uterus, increasing risk of spontaneous miscarriages, preterm labor, low-birth-weight infants, placental abnormalities [17]. These pregnancy-related complications are related with reduced uterine volume, damage of uterine vessels, myometrial fibrosis, endometrial injury.…”
Section: Impact Of Radiotherapymentioning
confidence: 99%